Transforming Oil Palm Trunk (OPT) Waste into Black Soldier Fly (BSF) Larval Biomass: Investigating Pretreatment and Enrichment - Handojo, Lienda A.; Permana, Agus Dana; Kresnowati , Made Tri Ari Penia; Utomo, Tanto Pratondo; Sumampouw, Giovanni Arneldi; Lugito, Graecia; Anderson, Reinhardt; Fauzani, Isna Dea; Deyanti, Nadya Putri; Amara, Satya; Pramudita, Daniel (ASEAN Journal of Chemical Engineering, 2025)
The Indonesian government’s palm oil replantation program has the potential to create an excess of oil palm trunks (OPT) in the field. Although there is an effort to obtain ethanol from the sap pressed from OPT, the OPT dregs (OPTD) remain as waste. This research investigates the potential of using OPTD as both a feed and growth medium for black soldier fly (BSF) larvae, which can be subsequently processed into animal feed. This manuscript focuses on the treatment of OPTD through maceration in water and palm oil mill effluent (POME), followed by the addition of supplementary materials, namely palm kernel meal (PKM), Azolla leaves, and solid decanter, to enhance the nutritional value and digestibility of the substrate. The effectiveness of these treatments is evaluated based on their waste-reducing capacity and the BSF larval growth. Macerating OPTD in 20% POME for 4 days was found optimal for enhancing the starch and sugar contents by 17% and 11%, respectively. The addition of PKM enhanced the growth of BSF larvae the most, resulting in a higher waste reduction index (WRI). However, it was not necessarily the most effective from the perspective of biomass conversion. The results here show that the treated OPTD mixture can serve as a viable complementary growth medium for BSF larvae.